Pengaruh Kepemilikan Institusional, Dewan Komisaris Independen, dan Komite Audit Terhadap Corporate Social Responsibility - Tri Yuliani Mega Putri; Paulus Yulius Fanggidae (STATERA: Jurnal Akuntansi dan Keuangan, 2021)
The purpose of this study was to obtain additional knowledge and empirical evidence regarding independent variables, namely the effect of institutional ownership, independent commissioners, and audit committees on Corporate Social Responsibility (CSR) in manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2019 period. The number of companies that were sampled in this study were 180 companies. The method of determining the sample used in this study used purposive sampling. Hypothesis testing in this study using multiple linear regression analysis method. The results showed that institutional ownership had no significant effect on Corporate Social Responsibility (CSR), while the independent board of commissioners and audit committee had a significant effect on Corporate Social Responsibility (CSR).